Evolution of technology in teaching: Blackboard and beyond in Medical Education - Muttappallymyalil, Jayakumary; Mendis, Susirith; John, Lisha Jenny; Shanthakumari, Nisha; Sreedharan, Jayadevan; Shaikh, Rizwana B (Nepal Journal of Epidemiology, 2016)
Teaching and learning - the passing of knowledge from one generation to another - has been in existence from the earliest times of human civilization. It began in 1801, with a large piece of slate hung on the wall in a school in Scotland to provide information to a large audience at one time. In the US by mid-19th century, every class room had a blackboard to teach students. The modern version of the blackboard is either green or brown board. This was introduced in late 1960s. The whiteboards came into use during the late 1980s. Projected aids have been used since 1420. The various devices used are the epidiascope, slide projector, overhead projector for transparencies and the micro projector. An instrument to project images from a horizontal surface onto a vertical screen was invented in the 1870s. By the 1960s, transparencies were in use in classrooms. The ‘Hyalotype’, a transparent image of a photograph using actual black and white photographs on a glass slide that could be projected was invented in 1851. By 1916, the German company Agfa started producing colored lantern slides. The first version of PowerPoint was released by Microsoft in the year 1990. Cell phones, palmtops, and handheld computers; tablets, laptops, and media players are included under mobile learning devices. With the evolution of technology, students achieved competence and interested in interactive learning. The education industry has moved from distance learning to e-learning and finally to m-learning as knowledge expanded exponentially and the demand escalated. While using teaching aids with advanced technology, we must not forget the lessons from the past, striking a balance between embracing new methods of teaching and learning while upholding the timeless principles of education. The newer educational technology can be part of a comprehensive system for lifelong education.